Snail Shells Adsorbent for Copper Removal from Aqueous Solutions and the Production of Valuable Compounds. (23rd September 2021) - Ouafi, Redouane; Asri, Meryem; Omor, Anass; Taleb, Mustapha; Rais, Zakia
Abstract : This research explored the efficiency of snail shells powder (SSP) for Cu(II) removal from aqueous solutions and the production of valuable compounds from the residual product. To confirm its chemical and mineral components, the material was characterized by different instrumental techniques. The effects of experimental parameters such as the pH of the solution, the effect of SSP dose, particle size, and initial concentration of Cu(II) on the removal process were studied. The removal of Cu(II) was reasonably fast to be completed within a time frame of 90 min. The kinetics following the pseudo-second-order model ( R 2 = 0.979) were better compared to the pseudo-first-order model ( R 2 = 0.896). The increase in pH values leads to an increase in the amount of Cu(II) adsorbed. Afterward, the adsorption capacity reaches stability at pH near 7. The maximum Cu(II) removal occurred with a mass of 8 g·L −1 and a particle size of 300 μ m. This particle size presents approximately 44.5% of SSP particles, which is the largest proportion of the sample as shown by particle size analysis. The adsorption isotherm was well described by Langmuir and Freundlich equations. The thermodynamic parameters values showed that the Cu(II) adsorption was a spontaneous and exothermic process. Furthermore, with the presence of CaCO3, the precipitation of Cu(II) in the form of posnjakite occurred with a high Cu(II) removal rate close to 99%. The residual SSP was used for the production of valuable compounds through the thermal decomposition process at various temperatures.